Structure and dynamics of nonionic surfactants adsorbed at vacuum/ionic liquid interfaces - Elola, Maria Dolores (2013)
Structural and dynamical properties related to the adsorption of nonionic surfactants at vacuum/ionic liquid interfaces were studied using molecular dynamics simulations. Specifically, the surface activity of pentaethylene glycol monododecyl ether (C12E5) was investigated at the free interface of an imidazolium-based room temperature ionic liquid (RTIL), at different surface densities. At low surface coverages, the incorporation of C12E5 does not produce meaningful changes in the vacuum/RTIL interface: the C12E5 hydrophobic tails remain entangled with those of the RTIL cation groups in the outer shell, whereas the C12E5 hydrophilic heads reside at an inner layer. At high surface coverages, the structure in the substrate—in terms of the features exhibited by the local density profiles—practically vanishes; the interface becomes wider and the surfactant molecules shift toward more external positions. Information about the local structure of the interface at high surface densities can be recovered by performing a tessellation procedure. For the sake of comparison, the surface behavior of two commonly used ionic surfactants, sodium dodecyl sulfate and dodecyl trimethyl ammonium chloride, were also studied. The modifications in the width and structure of the bare vacuum/RTIL interface due to the presence of the ionic surfactants are markedly milder than those observed for the nonionic surfactant. Moreover, the RTIL seemed to behave as a better solvent for the chloride counterions than for sodium ones; which were found to remain bound to the surfactant head groups. An analysis of the dynamics at the surface was also performed. Our results indicate that the presence of increasing amounts of nonionic surfactants leads to a gradual reduction of the mobility of the RTIL species. When ionic surfactants are adsorbed, these retardations are even more severe for the surfactant head groups, where the corresponding diffusion coefficients show reductions of practically 1 order of magnitude.